Akibat Hukum Rangkap Jabatan Notaris Sebagai Pimpinan Perguruan Tinggi - Wahyudi, Anis Rifdi; Handoko, Widhi (Notarius, 2023)
AbstractNotaries are public officials, carrying out their professions as per Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notaries and the Notary Code of Ethics. Public accountants are expected to comply with the law, including the denial of simultaneous situations as common authorities, advocates, lawful authorities and others. In addition, most notaries work as lecturers and serve as leaders of public and private universities, which raises the question of whether a notary can hold concurrent positions as leader of a university. This question can be argued and affects lawful conviction. This article intends to analyze whether a Notary who likewise fills in as a college chief truly abuses the Law on Notary Positions and the Notary Code of Ethics. This article is juridical regulating, utilizing optional information that contains essential, auxiliary and tertiary legitimate materials. This article is dissected subjectively. Concurrent positions as leaders of higher education institutions are not justified and violate the UUJN and the Notary Code of Ethics wherever they serve in state universities or those established by foundations.Keywords: double occupation; lecturer; notaryAbstrakNotaris adalah pejabat publik, menjalankan profesinya sesuai dengan Undang-Undang Nomor 2 Tahun 2014 tentang Perubahan atas Undang-Undang Nomor 30 Tahun 2004 tentang Jabatan Notaris (UUJN) dan Kode Etik Notaris. Notaris wajib menaati hukum termasuk larangan merangkap jabatan sebagai pejabat sipil, advokat, pejabat hukum dan lain-lain. Selain itu, demi beradaptasi dengan kurikulum pendidikan untuk kebutuhan praktek seorang Notaris dimasa yang akan datang, beberapa Perguruan Tinggi Program Magister Kenotariatan mengangkat seorang Notaris yang menjadi dosen pengajar untuk memiliki jabatan struktural. Situasi tersebut dihadapkan dengan aturan larangan rangkap Jabatan Notaris di dalam ketentuan UUJN. Artikel ini bertujuan untuk mengkaji apakah notaris yang juga berprofesi sebagai Pimpinan Perguruan Tinggi telah melanggar undang-undang Jabatan Notaris dan Kode Etik Notaris. Artikel ini bersifat yuridis normatif, dengan menggunakan data sekunder yang terdiri dari bahan hukum primer, sekunder dan tertier. Artikel ini dianalisis secara kualitatif. Merangkap jabatan sebagai pimpinan Perguruan Tinggi tidak dibenarkan dan melanggar UUJN dan Kode Etik Notaris dimanapun menjabat di perguruan tinggi negeri maupun yang didirikan oleh yayasan.Kata kunci: larangan; rangkap jabatan; notaris